Rhetorical Moves in Saint-Exupéry’s The Little Prince: A Genre Analysis - Tanusy, Jeanyfer; Tanto, Trisnowati (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2025)
This study examines the structural characteristics and communicative purposes of Saint-Exupery’s famous children novel The Little Prince. The research seeks to uncover the layers of storytelling that contribute to its enduring appeal and pedagogical value by analysing the novel’s structure. Employing a qualitative approach with the help of the corpus tool AntConc to collect data, the study analyses the moves and steps within the narrative to determine how each element functions to build the story's overall structure. The findings reveal that the novel, while ostensibly simple, contains complex narrative layers that present a modern approach to children's literature. This complexity not only engages young readers but also imparts wisdom and moral lessons in a nuanced manner. The study highlights the effectiveness of narrative structure in conveying deeper meanings and the importance of well-defined character roles in enhancing the story's communicative impact. Through this analysis, the research contributes to a broader understanding of narrative techniques in children's literature and their role in shaping young minds.